2009
DOI: 10.1177/0954008309348804
|View full text |Cite
|
Sign up to set email alerts
|

Film Properties of Polyazomethines (1). Effect of Incorporation of Intramolecular Cyclodehydrating Units

Abstract: Polyazomethines (PAzMs) were polycondensed from terephthalaldehyde (TPAL) with 2,2′bis(trifluoromethyl)benzidine (TFMB) and 2,2-bis[4-(4-aminophenoxy)phenyl] hexafluoropropane (HFBAPP). The PAzMs showed high solubility in N -methyl-2-pyrrolidone (NMP) ( > 15 wt.%) at room temperature and good film-formability. The film properties of the TPAL/TFMB-based PAzM copolymers were evaluated in the present study. In spite of their rod-like backbone structures, the PAzM films showed much higher coefficients of therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Indeed, we have previously observed that a polyazomethine (PAzM) copolymer film prepared by casting its NMP solution showed a very high CTE of 97 ppm K −1 in spite of its rigid chain structure, as depicted in Fig. . A comparison between the PAzM and the present copolyimides suggests that strong intermolecular forces (e.g.…”
Section: Resultsmentioning
confidence: 86%
“…Indeed, we have previously observed that a polyazomethine (PAzM) copolymer film prepared by casting its NMP solution showed a very high CTE of 97 ppm K −1 in spite of its rigid chain structure, as depicted in Fig. . A comparison between the PAzM and the present copolyimides suggests that strong intermolecular forces (e.g.…”
Section: Resultsmentioning
confidence: 86%
“…Accordingly, the gradual modulus decrease cannot be directly explained from a decrease in the crystallinity. Most likely, it is also not related to orientational relaxation with an increase in T a because PAzMs including flexible units essentially possess no practical chain alignment along the film plane ( X–Y ) direction (called in‐plane orientation) by solution casting . As a possible explanation, the modulus decrease tendency observed in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…We have previously investigated polyazomethine (PAzM) systems and obtained sufficiently flexible films with high T g. Poor attention has been paid so far to PAzM films for electronic applications, although main interests have been directed to PAzM fibers . The present work focused again on PAzM systems to investigate their potentiality as cover layer materials of FPCs.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study [19] it was shown that highly stiff/linear structures of PAzM systems prepared from terephthalaldehyde (TPAL) with 2,2 1 -bis(trifluoromethyl)benzidine (TFMB) and minor fractions of 2,2-bis(4-aminophenoxypheny)hexafluoropropane (HFBAPP) possessed excellent solubility in N-methyl-2-pyrrolidone (NMP) and led to the production of good films by solution casting. However, the PAzM films did not display low CTE characteristics which went against initial expectations.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach was to partially incorporate some intramolecular reactive sites (amic acid units) into the rod-like TPAL/TFMB-based PAzM backbone by using minor fractions of some tetracarboxylic dianhydride comonomers. The intramolecular thermal cyclodehydration (imidization) at the reactive sites induced a pronounced in-plane chain orientation phenomenon that was responsible for the low CTE characteristics, even when the reactive sites were introduced with a rather low content and/or a bent/flexible structure was formed after the reaction [19].…”
Section: Introductionmentioning
confidence: 99%